Sharing the Harvest: The Road to Self-Reliance, Report of the National Round Table on Aboriginal Economic Development and Resources - Canada. Royal Commission on Aboriginal Peoples (Minister of Supply and Services Canada, 1993)
The objectives of the National Round Table on Aboriginal Economic Development and Resources were to stimulate discussion of the economic development challenges facing Aboriginal peoples and to elicit suggestions on how these challenges can best be met. The results of the Round Table were to contribute to the formulation of the Royal Commission’s final recommendations. To bring a broad range of perspectives to the discussion, participants included those knowledgeable in economic development and resources issues and those with expertise in the creation and implementation of economic development initiatives benefitting Aboriginal communities — with a balance in terms of gender, age and Aboriginal identification. Economic development issues are very broad-ranging. To help focus discussion, five issue groups or themes were selected, and participants were asked to consider particular questions relating to each of the themes. Discussion papers were commissioned on each of the themes, and a series of examples or models of individual and community enterprise in economic development were presented. –Objectives, p. 1.
Last Modified: 2016-11-02

Report - Canada. Royal Commission on Aboriginal Peoples; Erasmus, George; Dussault, René (Royal Commission on Aboriginal Peoples, 1996)
The Report of the Royal Commission on Aboriginal Peoples (RCAP) concerns government policy with respect to the original historical nations of this country. Those nations are important to Canada, and how Canada relates to them defines in large measure its sense of justice and its image in its own eyes and before the world. The RCAP was established by Order in Council on August 26, 1991, and it submitted its report in October 1996. –Website description. Contents: v. 1. Looking forward, looking back (695 pages) – v.2. Restructuring the relationship (1,063 pages) – v.3. Gathering strength (668 pages) – v.4. Perspectives and realities (612 pages) – v.5. Renewal: A twenty-year commitment (609 pages).
Last Modified: 2016-11-02
Keywords: Canada; Canada. Autochtones; Canada. Native peoples; Conditions sociales. Autochtones; Custody; Deaths in custody. Government policy. Indians of North America; Economic conditions. Autochtones; Economic conditions. Indians of North America; Economic conditions. Inuit; Government relations. Health Services; Indigenous. Medicine; Traditional. Indians; North American. Inuits. Native peoples; Government relations. Indians of North America; Government relations. Inheemse volken; Government relations. Mtis; Government relations. Native peoples; Indians of North America; Politics and government. Native peoples; Politique et gouvernement. Autochtones; Relations avec l'tat. Autochtones; Social conditions. Indians of North America; Social conditions. Inuit; Social conditions. Native peoples